Bach Adsorption Study for the Extraction of Silver Ions by Hydrazone Compounds from Aqueous Solution - Mohamed Ali, Abdussalam Salhin; Abdul Razak, Norfarhah; Ab Rahman, Ismail (Hindawi Publishing Corporation, 2012)
Sorbent materials based on a hydrazone Schiff base compound, C14H11BrN4O4, were prepared either by immobilizing the ligand into sol-gel (SG1) or bonding to silica (SG2). The sorbent materials were characterized by FT-IR, EDX, SEM, TEM, and TGA. The sorption characteristics of a matrix of eight transition metal ions (Ag+, Cu2+, Co2+, Ni2+, Fe3+, Pb2+, Zn2+, andMn2+) using batch method were studied. Several key parameters that affected the extraction efficiency such as pH, contact time, metal ions concentration, and gel size (for SGl) were investigated and optimized. Under the optimized conditions, the physically immobilized hydrazone sorbent (SG1) exhibits highest selectivity towards Ag+ ions, while the chemically bonded hydrazone sorbent (SG2) exhibits high extraction for all metal ions tested. However, for practical applications such as the removal and preconcentration of Ag+, the physically immobilized sorbent (SG1) is preferred.